The Dynamics of Early Marriage in Terms of Islamic Family Psychology (Case Study in Sub-District of Bolo, Bima Regency) - Nadya Kurniyati; Atun Wardatun; Salimul Jihad (Jurnal Indonesia Sosial Teknologi, 2024)
Marriage life will always experience changes and ups and downs. Reviewing early marriage from the perspective of Islamic family psychology provides important insights into the dynamics which occur. It helps identify challenges and opportunities to improve the welfare and success of marriage. The objectives of this research were to understand and analyse the dynamics of early marriage in terms of Islamic family psychology and to understand and analyse the efforts of early marriage actors in dealing with family problems. This thesis used qualitative research based on field research; it used primary data sources obtained from the perpetrators of early marriage, parents, officials at the Religious Affairs Office (KUA) and religious leaders in the sub-district of Bolo, Bima Regency and secondary data sources. The data were collected by doing observation, interview, and documentation. The results of this research showed that 1) The dynamics of early marriage in terms of Islamic Family Psychology that every couple would experience challenges and changes over time, the factors which influenced failure in dealing with the dynamics of early marriage were the couple's psychological factors, lack of understanding and communication, not understanding the roles and responsibilities, lack of family support, not being able to adjust in marriage. 2) The efforts of early marriage actors in dealing with family problems were a) there were problems, b) there was no communication to solve, and c) they silenced and ignored each other. While other couples tried to understand each other, communicated and the support of direction from parents.